Ethical and Logistical Considerations of Multicenter Parental Bereavement Research - MEERT, KATHLEEN LYNN (2008)
BACKGROUND: Multicenter research has the potential to recruit participants with diverse racial, ethnic, and geographic backgrounds and is essential for understanding heterogeneity in bereavement. The National Institute of Child Health and Human Development Collaborative Pediatric Critical Care Research Network (CPCCRN) is a multicenter network charged with conducting research on the pathophysiology and management of critical illness in childhood. Among its research activities, the CPCCRN has undertaken research in parental bereavement because most childhood deaths in the United States occur in hospitals, primarily in critical care units. OBJECTIVE: The purpose of this paper is to discuss ethical and logistical issues found by the CPC-CRN to be problematic to multicenter research with bereaved parents and to explore research strategies that may be practicably implemented. RESULTS: Ethical and logistical challenges encountered by the CPCCRN included issues of privacy; confidentiality; voluntariness; minimizing risks; working with multiple institutional review boards; researcher qualifications, training and support; and methods of data collection. Strategies to address these challenges included local recruitment of participants; flexibility in consent methods across sites; participant options for methods of data collection; involvement of local bereavement support services; central training of researchers with systematic monitoring and opportunitieas for support; and use of a secure Web-based collaborative workspace. CONCLUSIONS: Multicenter parental bereavement research has distinct ethical issues that must be addressed by the logistics of the research plan. Greater attention to the issues identified may facilitate research to reduce adverse mental and physical health outcomes in a diverse population of bereaved individuals.